Validation of Nova Stat Profile Prime Plus point-of-care testing for dialysis in South Africa - Kagiso M. Masemola; Ngalulawa Kone; Chemedzai Chikomba; Siyabonga Khoza (African Journal of Laboratory Medicine)
Background: Chronic kidney disease is a global health crisis, and delays in laboratory testing worsen outcomes. Point-of-care testing (POCT) has shown utility in various settings, but its performance at high creatinine levels seen in advanced chronic kidney disease is variable.